Education and Intended Number of Children in Germany, Moldova and Norway: An International Comparison Using FReDA and GGS-II-data - Sandra Krapf; Isabella Buber-Ennser; Martin Bujard (Comparative Population Studies, 2023)
In this study, we compare the intended number of children in Germany, Moldova and Norway in 2020 and 2021, during the COVID-19 pandemic. In a first step, we compare the intended number of children (including children born) in the newly available Generations and Gender Survey round 2 (GGS-II) and the German FReDA-GGS data. In a second step, we estimate the number of further intended children with multinomial logistic regression models. The results reveal considerable differences across the three countries. Respondents in Moldova plan to have rather large families (on average 3.3 children, including children born), whereas individuals in Norway and Germany intend to have 2.0 and 1.8 children, respectively. In the multinomial logistic regression analyses, we find differences in the association of educational level and fertility plans by gender and country. In Germany, education is positively related to the intention to have further children. This pattern is more pronounced for women than for men. Furthermore, this association is also found among Norwegian men. In Moldova, we find only weak evidence for this association. For Norwegian women, education and the intention to have further children also seem to be unrelated. While most data about the intended number of children refer to the 2000s or earlier, we contribute to the literature by providing recent insights on the intended number of children in three European countries, including Moldova, a country that is understudied in demographic research.